Impacts of invasive plants on resident animals across ecosystems, taxa, and feeding types: a global assessment. (11th December 2015) - Schirmel, Jens; Bundschuh, Mirco; Entling, Martin H.; Kowarik, Ingo; Buchholz, Sascha
Abstract: As drivers of global change, biological invasions have fundamental ecological consequences. However, it remains unclear how invasive plant effects on resident animals vary across ecosystems, animal classes, and functional groups. We performed a comprehensive meta‐analysis covering 198 field and laboratory studies reporting a total of 3624 observations of invasive plant effects on animals. Invasive plants had reducing (56%) or neutral (44%) effects on animal abundance, diversity, fitness, and ecosystem function across different ecosystems, animal classes, and feeding types while we could not find any increasing effect. Most importantly, we found that invasive plants reduced overall animal abundance, diversity and fitness. However, this significant overall effect was contingent on ecosystems, taxa, and feeding types of animals. Decreasing effects of invasive plants were most evident in riparian ecosystems, possibly because frequent disturbance facilitates more intense plant invasions compared to other ecosystem types. In accordance with their immediate reliance on plants for food, invasive plant effects were strongest on herbivores. Regarding taxonomic groups, birds and insects were most strongly affected. In insects, this may be explained by their high frequency of herbivory, while birds demonstrate that invasive plant effects can also cascade up to secondary consumers. Since data on impacts of invasive plants are rather limited for many animal groups in most ecosystems, we argue for overcoming gaps in knowledge and for a more differentiated discussion on effects of invasive plant on native fauna.